Sifat Fisikokimia dan Aktivitas Antioksidan Crude Fukoidan Hasil Ekstraksi dari Sargassum cinereum - Liliek Nurhidayati; Yashinta Fitriani; Syamsudin Abdillah; Esti Mumpuni; Mohamad Rafi (JURNAL ILMU KEFARMASIAN INDONESIA, 2020)
Brown seaweed has been known as a fucoidan source that has various biological activities. Fucoidan could be obtained by various extraction methods. This study aims to extract, characterize and to evaluate the antioxidant activity of crude fucoidan extracted from Sargassum cinereum. Extraction was carried out by refluxing at 100oC for 4 and 5 hours and then precipitated with ethanol. The crude fucoidan was brown powder. The yield with 4 hours extraction time was 2.78% which did not differ significantly from the 5 hours extraction time. Phytochemical screening of crude extract showed that beside fucoidan there were flavonoids, saponins, steroids, triterpenoids, and tannins. The extraction with duration of 4 hours and 5 hours had sulfate content of 16.31% and 11.22%, total carbohydrate content were 22.94% and 22.85%, and in the FTIR spectrum showed OH absorption bands of carbohydrates, fucose, sulfates and uronic acid. Testing of antioxidant activity using the DPPH (1,1-diphenyl-2-picrylhyrazyl) free radical inhibition method produced IC50 values ​​of 721.9 µg/ml and 749.9 µg/ml respectively and it was concluded that crude fucoidan of Sargassum cinereum had weak antioxidant activity.